A cold spray-based novel manufacturing route for flexible electronics. (27th January 2023) - Akin, Semih; Jo, Seunghwan; Jun, Martin Byung-Guk
Abstract: In this research, we propose a cold spray-based novel manufacturing route that enables the custom production of flexible electronics (FE) at high spatial resolution without a need of high-temperature post-sintering process. The proposed manufacturing route sequentially comprises: (1) cold spray metallization; (2) femtosecond laser machining; and (3) ultrasonic plastic welding. First, the flexible polymer ( i.e., PET) surface is metallized by cold spray direct writing of Tin (Sn) particles under vacuum-and mask-free conditions. The as-metallized polymer film is then precisely cut into arbitrarily designed high-resolution electrodes ( i.e., 500 μm linewidth) by femtosecond laser machining. Lastly, the laser-cut electrodes are joined onto a base polymer substrate via ultrasonic plastic welding to constitute mechanically resilient and conformal FE. In this way, the proposed route enables exploiting the unique features of cold spray deposits in FE ( e.g., strong adhesion, high conductivity, minimal thermal input). The resultant printings show excellent electrical conductivity (1.08 × 10 6  S·m −1 ), flexibility (60 % elongation), and adhesion strength without significantly compromising intrinsic polymer and functional coating properties. Moreover, a serpentine-shaped flexible microheater (10 × 10 mm 2 ) is also fabricated to demonstrate the viability of the introduced platform in flexible microelectronics. This work potentially provides a promising route toward the rapid, scalable, and cost-effective production of high-resolution and high-performance FE in a mechanically resilient and conformal manner. Highlights: A novel manufacturing route is proposed for printed flexible electronics (FE). Cold spray technique is used for direct conductive metallization on flexible polymers. Custom-designed high-resolution FE with excellent electrical conductivity and adhesion strength are achieved. The applicability of the proposed route is also validated for thermosetting polymer substrates.